Reversible binding of dihydrogen in multimetallic complexes - Weller, A; McIndoe, J (2007)
The interaction of hydrogen with metal surfaces is one of the most important and fundamental processes in the chemical industry. Hydrogen is also strongly tipped to play a central role in new challenges that are emerging in terms of climate change and energy supply, and the reversible binding of H 2 to suitable materials will play a keystone role in the realisation of the hydrogen economy. The reversible interaction of hydrogen with multimetallic centres is also an important theme in biological processes; the role of hydrogenases in the metabolism of H2 is an example. Thus the reversible interaction of H2 with multimetallic metal complexes is an area that spans considerable breadth. This review is concerned with the reversible interaction of H2 with soluble multimetallic complexes, defined broadly as clusters, in which there are no other ligands lost or gained in the process. The review is organised under the subheadings: equilibrium reversible (H2 is lost upon removal of the H2 atmosphere), thermally reversible or reversible when placed under vacuum, photochemically reversible and electrochemically reversible interactions; a brief outline of reversible H2 binding in systems of biological interest; giant metal clusters that display reversible H2 binding. © Wiley-VCH Verlag GmbH and Co. KGaA, 2007.